2022
DOI: 10.1111/hdi.13044
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the arterial needle bevel position on puncture pain and postremoval bleeding time in hemodialysis patients: A self‐controlled, single‐blind study

Abstract: This study aimed to investigate the effect of the bevel orientation (facing upwards or downwards towards the skin) of the needle inserted into the arterial limb of the arteriovenous fistula (AVF) on puncture pain and postremoval bleeding time.Methods: This study, using a single-blind crossover design, was conducted on 35 maintenance hemodialysis patients who had been dialyzed for at least 6 months and in whom blood access was via an AVF. AVF cannulation was performed with the needle bevel pointing upward in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 13 publications
2
4
0
Order By: Relevance
“…Montero et al found that puncture‐related pain was less when the needle bevel was oriented downward during insertion; however, they were unable to correlate puncture pain with incision size. Ozen et al, in their study of 35 patients, reported a significant reduction in pain during access puncture using the downward bevel technique 5 . In our study, needle orientation was not associated with puncture‐associated pain.…”
Section: Discussionsupporting
confidence: 53%
See 3 more Smart Citations
“…Montero et al found that puncture‐related pain was less when the needle bevel was oriented downward during insertion; however, they were unable to correlate puncture pain with incision size. Ozen et al, in their study of 35 patients, reported a significant reduction in pain during access puncture using the downward bevel technique 5 . In our study, needle orientation was not associated with puncture‐associated pain.…”
Section: Discussionsupporting
confidence: 53%
“…Ozen et al, in their study of 35 patients, reported a significant reduction in pain during access puncture using the downward bevel technique. 5 In our study, needle orientation was not associated with puncture-associated pain. The pain reported by our patients on access puncture was quite mild, averaging only 1 on a 0-10 intensity scale.…”
Section: Discussionsupporting
confidence: 39%
See 2 more Smart Citations
“…Hemodialysis patients with an arteriovenous fistula (AVF) or arteriovenous graft (AVG) are at increased risk of bleeding due to the coagulopathy of end-stage kidney disease [ 1 ] and the use of systemic anticoagulation in the hemodialysis circuit [ 2 ]. The risk of prolonged bleeding specifically after needle removal from AVF or AVG cannulation sites is also impacted by needle position [ 2 , 3 ] cannulation technique (buttonhole versus rope-ladder) [ 4 ], vascular access integrity, namely whether there is associated pseudoaneurysm/aneurysm, stenosis or infection [ 5 ]. Prolonged post-cannulation bleeding is associated with poor outcomes including increased rates of anemia [ 6 ], quality of life disruptions [ 7 ], and fatal catastrophic hemorrhage [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%